Impact of Finishing Protocol on the Color Stability of CAD/CAM Ceramics: A Systematic Review - Alencar, Cristiane de Melo [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Silva, Aryvelto Miranda [UNESP]; Ortiz, Mariangela Ivette Guanipa; Lima, Debora Alvez Nunes Leite; Campos, Edson Alves de [UNESP] (Quintessence Publishing Co Inc, 2022)
Purpose: To analyze the current evidence on the impact of surface finishing protocols (manual polishing vs glazing) on the color stability of in vitro pigmentation of CAD/CAM ceramics. Materials and Methods: Five electronic databases were searched on February 12, 2020. In vitro experimental studies were included based on the following PICO strategy: intervention = surface treatment of CAD/CAM ceramics with glazing agents; comparison = surface treatment of CAD/CAM ceramics with manual polishing; and outcome(s) = color stability. Two reviewers independently assessed the risk of bias. Results: Among 1,390 articles that were screened, 6 in vitro studies were considered for qualitative analysis. Five articles confirmed changes in the color of ceramics when they were immersed in pigmented solutions. One article investigated the color stability of samples after ultraviolet (UV) aging. Among the 6 studies analyzed, 4 showed clinically acceptable color alteration values (represented by AE) irrespective of the finishing protocol applied. Two articles presented clinically unsatisfactory color variation (AE > 3.3 and AE > 2.7) following mechanical polishing of a zirconia-reinforced lithium silicate ceramic. Coffee and red wine proved to be the beverages with the greatest potential for ceramic pigmentation. Only 1 article had a high risk of bias. Condusion: For clinicians, most of the included studies demonstrated that both manual polishing and glaze application can prevent significant color alterations on CAD/CAM ceramic surfaces. However, due to the relatively limited amount of evidence to support this conclusion, further studies must be conducted. Int i Prosthodont 2022;35